RELEASING THE WELDED PARTS THROUGH THERMAL TREATMENTS - Alin STĂNCIOIU (Fiabilitate şi Durabilitate)
Heat treatments before welding are applied to steels in order to bring them to the state in which they can best support the welding operation (normalization, stress relief or recrystallization). Thermal treatments during welding include pre-heating, post-heating and the combination of pre-heating and post-heating. Thermal treatments after welding that are applied to remove the unwanted effects caused by the welding operation.